The Dairy Sector in the Central European Candidate (CEC) Countries - The Status of Restructuring and Future Challenges - Monika Hartmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
The dairy sector in the CEC countries had to cope with tremendous adjustment pressures in the 90ies. Privatization and liberalization contributed to intense competition on the CEC countries' dairy market. Major problems that impede the competitiveness of this sector are a considerable fragmentation of the dairy processing industry, pronounced excess capacities, high seasonality of milk production and low investment activities. The latter delays the modernization of processing technologies and thus hinders quality improvements and the adjustments of hygienic conditions as well as product and process standards to EU norms. These problems are common to all CEC countries, though to different degrees. In addition, especially in Bulgaria and Romania, but also in Poland, Lithuania and Latvia the dairy industry is burdened by the low quality of the raw material and high milk collecting costs. Improving technical as well as economic efficiency in the primary and processing sector and seeking strategic alliances are necessary to secure the competitiveness of the CEC countries' dairy industry in EU and world markets.
Keywords: 330; Milchverarbeitung; Internationaler Wettbewerb; EU-Mitgliedschaft; Wirtschaftliche Anpassung; EU-Staaten; Osteuropa